ADOLESCENT LONELINESS IN ORPHANAGES: ROLES OF SELF-COMPASSION AND SOCIAL SUPPORT - Apriyeni, Emira; Patricia, Helena; Rahayuningrum, Dwi Christina (Menara Medika, 2025)
Background: Orphanage adolescents are vulnerable to experiencing psychological issues, one of which is loneliness. Loneliness among orphaned adolescents tends to be caused by unmet social support, resulting in dissatisfaction with their social relationships. One effective way to reduce loneliness in orphaned adolescents is through self-compassion. Objective: This study aims to explore the relationship between self-compassion and social support with loneliness among adolescents in the Minangkabau Islamic boarding school orphanage, Padang. Method: This research employed a quantitative approach with a cross-sectional design. The population consisted of 365 adolescents from the Minangkabau Islamic boarding school orphanage, with a sample of 155 participants selected using a simple random sampling technique. Data were collected using the UCLA Loneliness Scale (Version 3), the Self-Compassion Scale, and the Multidimensional Scale of Perceived Social Support (MSPSS). Results: The study found that the average loneliness score was 43.02, self-compassion was 82.66, and social support was 29.51. A significant relationship was found between self-compassion (p-value = 0.000; r = -0.457) and social support (p-value = 0.000; r = -0.407) with the level of loneliness among adolescents in the orphanage. Conclusions: Based on these findings, it is recommended that orphanage guardians develop supportive policies, such as implementing counselling services and offering extracurricular activities to help reduce feelings of loneliness.